Ways to improve budget forecasting of tax revenues from subsoil users in the Republic of Uzbekistan (Eurasian Research Bulletin, 2024)
This article is devoted to the consideration of the issues on regulating taxation of subsoil users, ensuring the required level of collection of taxes and other compulsory payments. In addition, the article contains proposals on improving the services in reliance upon cooperation of taxpayers in the implementation of tax administration and tax obligations